A method for identifying geometrical defects and stress concentration zones in MMM technique. (October 2019) - Sun, Le; Liu, Xin'en; Niu, Hongpan
Abstract: Metal magnetic memory (MMM) technique is a kind of passive magnetic non-destructive inspection technique sensitive to early damage due to stress concentration in ferromagnetic components. However, geometrical defects and stress concentration zones probably coexist in an inspected component, which will make trouble for damage evaluation. In the paper, a 3-Dimensional (3D) numerical simulation based on a stress-induced magnetic anisotropic constitutive model is employed to produce the MMM signals of an ×80 pipeline steel plate with a center hole stretched in the geomagnetic field. The effects of the hole and the nearby stress-concentration zones on the MMM signal characteristics are respectively studied, and then a simple and convenient MMM signal processing method is proposed to identify two kinds of damage. This work is useful for improving accuracy of the MMM technique in damage evaluation.